Следящая система с бесконтактным двигателем постоянного тока и нелинейным изодромным регулятором - A. S. Mikhalev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2011)
The paper shows that it is possible to exclude an average component of a forced tracing error in auto-oscillating systems due to switching-off an output integrator coordinate from a direct system tract within those intervals when speed signs of an input axis and engine do not coincide with each other. Investigation accuracy of such systems using a method of harmonic linearization is quite sufficient for engineering calculations.